Serum Paraoxonase activity in relation to lipid profile in Age-related Macular Degeneration patients. (November 2016) - AnandBabu, Kannadasan; Bharathidevi, S.R.; Sripriya, Sarangapani; Sen, Parveen; Prakash, Vadivelu Jaya; Bindu, Appukuttan; Viswanathan, Natarajan; Angayarkanni, Narayanasamy
Abstract: Age-related Macular Degeneration (AMD) is a multifactorial disease causing visual impairment in old age. Oxidative stress is one of the main contributors for the disease progression. Paraoxonase (PON), a HDL-resident antioxidant enzyme which removes oxidized low density lipoprotein (oxLDL), which is not studied much in AMD. This study assesses the PON activities in relation to the lipid status and genetic variants in AMD patients. In this prospective case-control study, a total of 48 AMD patients and 30 unrelated healthy controls were recruited. The serum oxLDL and Plasma Homocysteine (Hcy) levels were estimated by ELISA. Plasma Homocysteine thiolactone (HCTL) was estimated by HPLC. Serum PON activities were estimated by spectrophotometry. PON gene expression was assessed by qPCR and protein expression by western blot, immunofluorescence and FACS analysis. Two known single nucleotide polymorphisms (SNPs) in the coding region of PON1, Q192R and L55M variants were checked in the AMD patients and controls and their association with PON activity and lipid levels were determined. Serum paraoxonase (PONase) and thiolactonase (PON-HCTLase) activities were significantly elevated in AMD patients than in controls apart from elevated serum levels of total cholesterol (TC), triglycerides (TG), oxLDL. While serum LDL levels in AMD patients correlate positively with PON HCTLase activity, the serum high density lipoprotein (HDL) correlates with both PONase and PON-HCTLase activities. However, multiple regression analysis showed that, amongst the parameters, only serum TG was a significant risk factor for AMD, after adjusting for demographic parameters as well as cataract. PON2 was significantly increased at the level of gene expression (p = 0.03) as seen in circulating peripheral blood mononuclear cells (PBMC) of AMD patients possibly mediated by the transcription factor SP1, that showed 2-fold increase. PON1 and 2 protein expressions also showed significant increase in the PBMC of AMD patients. At serum level, PON1 protein was significantly increased in AMD patients. Cholesterol transporters such as CD36, SR-B1 and ABCA1 gene expressions were also found to be higher (1.5, 1.9 and 2.4-fold respectively) in AMD, though not statistically significant. While the wet AMD (CNV) was found to be associated with increase in oxLDL and serum PONase activity, the dry AMD was associated with increased HDL and serum PON-HCTLase activity. The genotype and allele frequencies of Q192R & L55M were not significantly different between AMD patients and controls. However, altered lipid status and PON activities were associated with the genotype in AMD patients. A higher enzyme activity was observed for the RR genotype of Q192R in the cohort, irrespective of case and control. Thus the PON genotype and phenotype seem to play a role in the pathogenesis of AMD. Highlights: Serum Triglyceride is a significant risk factor for age-related macular degeneration (AMD). Serum paraoxonase (PONase) and thiolactonase (PON-HCTLase) activities of the PON protein in serum HDL are elevated in AMD. PON2 gene and protein expressions are increased in circulating peripheral blood mononuclear cells (PBMC) of AMD patients. First report on elevated serum PON1 protein acquired into circulating PBMC of AMD patients. Altered lipid status and PON activities are associated with the genotype in AMD patients.